ASSESSMENT OF ECONOMIC EFFECTIVENESS OF RESULTS OF INTELLECTUAL ACTIVITY - Pavel A. Kalachikhin (Статистика и экономика, 2016)
Commercialization and capitalization of the results of intellectual activity are studied in the article. Dependence of the innovative potential on the indicators of economic efficiency is investigated. A review of the ways of assessment of the market cost of the results of intellectual activity and the monetary income from the commercialization of the results of intellectual activity at innovative market is made. The methods of the calculation of this efficiency are offered as components of the innovative potential.